2022
DOI: 10.3390/rs14122928
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Vegetation Heights and Their Seasonal Changes in the Western Namibian Savanna Using Spaceborne Lidars

Abstract: The Ice, Cloud, and Land Elevation Satellite-2 (ICESat-2) with its land and vegetation height data product (ATL08), and Global Ecosystem Dynamics Investigation (GEDI) with its terrain elevation and height metrics data product (GEDI Level 2A) missions have great potential to globally map ground and canopy heights. Canopy height is a key factor in estimating above-ground biomass and its seasonal changes; these satellite missions can also improve estimated above-ground carbon stocks. This study presents a novel S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…We extracted the laser point data for Chongqing City for the entire year of 2020, totaling 74,972 control points. Previous studies [48,49] have indicated that ATLAS photon data may be influenced by various factors such as slope, cloud cover, and imaging time. These factors can lead to a reduction in photon energy and introduce errors in distance measurements.…”
Section: Pre-processing Of Icesat-2 Atl08 Datamentioning
confidence: 99%
“…We extracted the laser point data for Chongqing City for the entire year of 2020, totaling 74,972 control points. Previous studies [48,49] have indicated that ATLAS photon data may be influenced by various factors such as slope, cloud cover, and imaging time. These factors can lead to a reduction in photon energy and introduce errors in distance measurements.…”
Section: Pre-processing Of Icesat-2 Atl08 Datamentioning
confidence: 99%